Gestational hypertension, preeclampsia and intrauterine growth restriction induce dysregulation of cardiovascular and cerebrovascular disease associated microRNAs in maternal whole peripheral blood - Hromadnikova, Ilona; Kotlabova, Katerina; Hympanova, Lucie; Krofta, Ladislav (Thrombosis research, 2016)
AIMS: To demonstrate that pregnancy-related complications are associated with alterations in cardiovascular and cerebrovascular microRNA expression. Gene expression of 29 microRNAs (miR-1-3p, miR-16-5p, miR-17-5p, miR-20a-5p, miR-20b-5p, miR-21-5p, miR-23a-3p, miR-24-3p, miR-26a-5p, miR-29a-3p, miR-92a-3p, miR-100-5p, miR-103a-3p, miR-122-5p, miR-125b-5p, miR-126-3p, miR-130b-3p, miR-133a-3p, miR-143-3p, miR-145-5p, miR-146a-5p, miR-181a-5p, miR-195-5p, miR-199a-5p, miR-210-3p, miR-221-3p, miR-342-3p, miR-499a-5p, and miR-574-3p) was assessed in maternal whole peripheral blood, compared between groups (39 gestational hypertension, 68 preeclampsia, 33 intrauterine growth restriction and 20 normal pregnancies) and correlated with the severity of the disease with respect to clinical signs, delivery date, and Doppler ultrasound parameters. Initially, selection and validation of endogenous controls for microRNA expression studies in patients affected by pregnancy-related complications have been carried out. RESULTS: The expression profile of microRNAs was different between pregnancy-related complications and controls. The down-regulation of miR-100-5p, miR-125b-5p and miR-199a-5p was a common phenomenon shared between gestational hypertension, preeclampsia, and intrauterine growth restriction. Moreover, IUGR pregnancies induced down-regulation of miR-17-5p, miR-146a-5p, miR-221-3p and miR-574-3p in maternal circulation. Irrespective of the severity of the disease, preeclampsia was associated with the dysregulation of miR-100-5p and miR-125b-5p and IUGR with dysregulation of miR-199a-5p. Preeclampsia requiring termination of gestation before 34 weeks was associated with down-regulation of miR-146a-5p, miR-199a-5p and miR-221-3p. Weak negative correlation between miR-146a-5p and miR-221-3p expression and the pulsatility index in the umbilical artery was found. Additional microRNAs (miR-103a-3p, miR-126-3p, miR-195-5p and miR-499a-5p) showed a trend to down-regulation in appropriate pregnancy-related complications. CONCLUSION: Epigenetic changes are induced by pregnancy-related complications in maternal whole peripheral blood.
Keywords: hypertenze indukovaná těhotenstvím; Cerebrovascular Disorders; MicroRNAs; Preeclampsia; Genetic Predisposition to Disease; růstová retardace plodu; mikro RNA; Pregnancy; Pre-Eclampsia; epigeneze genetická; těhotenství; Gestational hypertension; Adult; Hypertension, Pregnancy-Induced; dospělí; preeklampsie; MicroRNA; cerebrovaskulární poruchy; kardiovaskulární nemoci; lidé; Fetal Growth Retardation; ženské pohlaví; Intrauterine growth restriction; Humans; Cardio/cerebrovascular diseases; Cardiovascular Diseases; Female; genetická predispozice k nemoci; Epigenesis, Genetic